IMMU-22. PHASE IB IMMUNOTHERAPY CLINICAL TRIAL WITH THE USE OF AUTOLOGOUS DENDRITIC CELLS PULSED WITH AN ALLOGENIC TUMORAL CELL LINES LYSATE IN PATIENTS WITH NEWLY DIAGNOSED DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (4th December 2020) - Madrid, Andres Morales La; Mora, Jaume; Cruz, Ofelia; Lopez, Vicente Santa-Maria; Perez-Jaume, Sara; Guillen, Antonio; Paco, Sonia; Carcaboso, Angel M; Puerta, Patricia; Salvador, Noelia; Juan, Manuel; Benitez-Ribas, Daniel; et al.
Abstract: BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is a lethal condition, and therefore novel approaches are needed. Monocyte-derived dendritic cells (mDCs) pulsed with tumor antigens, as professional antigen-presenting cells, are a promising strategy for immunotherapy of invasive brain tumors. METHODS: Our Ib pilot study explored the use of immunotherapy with mDCs for the treatment of newly diagnosed DIPG. Patient′s mDCs were extracted after irradiation and were primed with an allogenic tumor lysate from five patients with K27M-mutated DIPGs. The principal goal of this study was to establish the feasibility and safety of the intradermic administration of these mDC vaccines in patients with DIPG. In the absence of progression, patients received maintenance boosts of tumor lysate. Additionally, we evaluated the non-specific and antitumoral immune response generated in peripheral blood mononuclear cells (PBMC) and in cerebrospinal fluid (CSF) cells. RESULTS: Nine patients were included in the study (2016–2018). Vaccines fabrication was feasible and administered in all cases without grade 3 or 4 toxicities. KLH (9/9 patients) and antitumor (8/9 patients) specific responses were identified in PBMC. Immunological responses were also confirmed in T-lymphocytes from the CSF of two patients. Twenty-four month overall survival and progression free survival was 33.3% (95 % CI 13.2% to 84.0 %) and zero, respectively. DISCUSSION: These results demonstrate that mDC vaccination is feasible, safe, and generates a DIPG-specific immune response detected in PBMC and CSF. There was a trend in improved OS when compared to historic controls. This strategy shows a promising immunotherapy backbone for future combination schemas.